Climate Risk & Vulnerability (CR&V) assessment for climate services: Rice-shrimp production and value chain - Mekong River Delta, Viet Nam - Vu Thi, Ngoc Bich; Le, Thi Tam; Giles, James; Swaans, Cornelis (2023)
As part of the CGIAR Initiative on Asian Mega-Deltas, a scoping study was completed by the end of 2022 to prioritize key delta-oriented production systems and value chains in Viet Nam's Mekong River Delta (MRD) (Gonsalves et al., 2022). Rice, rice-shrimp, and fruit trees production systems and value chains were selected based on a set of criteria including production, economic and nutritional value, climate change and impact, and potential benefit of climate services with specific attention to the role of women and smallholders. To better understand the selected commodity production systems in the MRD, an additional value chain climate risk and vulnerability assessment was made. This report focuses on rice shrimp production and its value chain. Since the rice value chain is already covered in a separate climate risk and vulnerability assessment, we will mainly focus on shrimp as part of this system.